ANALISIS PENGARUH STATUS BEKERJA TERHADAP JENIS KELAMIN DAN UMUR DENGAN PENDEKATAN BINARY LOGISTIC REGRESSION - Syamsul Rizal; Imaroh Izzatun Nisa; Moh. Yamin Darsyah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
One of method of Data Analysis Category used to determine the effect of the relationship with the response variable of type nominal is using Binary LogisticRegression (BLR) approach. BLR is used for data whose response variable isdata consisting of two categories, with one predictor variable or more, bothcategorical and continuous. In determining the degree of workforce inIndonesia, one indicator that can be used is the status of working. Status workdefined into two, namely the status is still working and the status does not work.Variabel used in this study is the working status ( Y) as the response variablewith category 1 is still working, category 0 does not work, while the predictorvariables are education level (X1) and gender (X2). There are 2 variables thataffect the model of education variables (X1) and age (X2). The accuracyclassification is 87%. Keywords: Working Status, BLR,Classification